The Actualization of Sustainable Development Goals (SDGs) In Indonesia Economic Growth an Islamic Economic Perspective - Wartoyo Wartoyo; Nur Haida (UIN Mataram, 2023)
ABSTRAK Islamic economics has goals that are aligned with the SDGs, where economic growth mustnot come at the expense of greater things such as environmental damage and human rights.The purpose of this study is to find out how the actualization of the SDGs program oneconomic growth in Indonesia is viewed from an Islamic economic perspective. This researchuses descriptive qualitative methods with literature studies related to theoretical studies andother references related to economic growth. The results of this study conclude that theactualization of the SDGs program in economic growth in Indonesia has not been fullyachieved, even though it has gone on the right track. The indicator is that the efforts so farhave been made aimed at alleviating poverty through fiscal policy accompanied bymobilization of zakat and productive waqaf, reducing unemployment and improvingcommunity welfare through direct assistance programs and business capital assistance.Efforts to preserve the environment have also begun intensively by reclaiming beaches,reforesting forests and reducing the use of fossil fuels through the conversion of conventionalvehicles to electric vehicles. All these efforts are in line with the goals of the SDGs as well asthe goals of the Islamic economy.